Microbial and biotechnological approaches to harness agricultural wastes for sustainable phosphorus management in crop production - Oubohssaine, Malika; Rabeh, Karim; Hnini, Mohamed; Aurag, Jamal (Frontiers in Agronomy, 2025)
Global phosphorus (P) management faces critical challenges driven by rising demand, inefficient fertilizer use, and environmental degradation. The depletion of finite phosphate rock reserves, coupled with low crop uptake efficiencies and substantial soil fixation, underscores the unsustainability of the current linear phosphorus economy. These inefficiencies contribute to eutrophication, biodiversity loss, and escalating economic burdens on farmers and governments. In response, this review explores a systems based approach centered on circular strategies for P recovery from agricultural wastes such as manure, crop residues, and food industry byproducts, which offer renewable alternatives while enhancing soil health and carbon sequestration. Biological treatments, including composting, vermicomposting, and anaerobic digestion, demonstrate promising recovery efficiencies but remain limited by scalability, nutrient imbalances, and pollutant risks. Microbial and biotechnological processes, such as phosphate solubilizing bacteria, may play crucial roles in enhancing P availability through enzymatic and acidification mechanisms. Integrating these tools into crop production, particularly via precision application and microbial consortia design, can significantly reduce reliance on mined P, mitigate environmental harm, and bolster agricultural sustainability. Future directions must prioritize omics driven inoculant development, regulatory frameworks for biofertilizer deployment, and climate resilient microbial strategies to ensure resilient phosphorus cycling in agroecosystems.